Perceived posttraumatic growth after interpersonal trauma and subsequent well-being among young Colombian adults: A longitudinal analysis - Chen, Zhuo Job; Bechara, Andrea Ortega; Cowden, Richard G.; Worthington, Everett L. (Frontiers in Psychology, 2022)
Research has shown that people often report self-perceived growth as a result of dealing with a potentially traumatic event, but relatively few methodologically rigorous studies have examined whether perceived posttraumatic growth is associated with improved subsequent well-being across a wide range of outcomes. In this three-wave longitudinal study of Colombian emerging adults (n = 636), we examined the associations of perceived posttraumatic growth with 17 well-being outcomes across domains of psychological well-being (i.e., self-rated mental health, meaning in life, sense of purpose, happiness, life satisfaction), psychological distress (i.e., anxiety symptoms, depression symptoms, subjective suffering), social well-being (i.e., content with relationships, satisfying relationships, loneliness), physical well-being (i.e., self-rated physical health, sleep quality), and character strengths (i.e., state hope, trait forgivingness, orientation to promote good, delayed gratification). Using an outcome-wide analytic design that adjusted for a range of covariates assessed in Wave 1, we found that overall perceived posttraumatic growth assessed in Wave 2 was robustly associated with improvements in one or more facet of each well-being domain (15/17 outcomes in total) assessed approximately six months later in Wave 3. Our findings suggest that perceived posttraumatic growth may contribute to individual well-being over the longer-term.